1998
DOI: 10.1038/bjc.1998.629
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial comparing methotrexate and vinblastine (MV) with cisplatin, methotrexate and vinblastine (CMV) in advanced transitional cell carcinoma: results and a report on prognostic factors in a Medical Research Council study

Abstract: of CMV. This translates to an absolute improvement in 1-year survival of 13%, 16% in MV and 29% in CMV. The median survival for CMV and MV was 7 months and 4.5 months respectively. Two hundred and eight patients objectively progressed or died. The hazard ratio was 0.55 (95% Cl 0.41-0.73, P-value = 0.0001) in favour of CMV. Two hundred and nine patients symptomatically progressed or died. The hazard ratio was 0.48 (950°o Cl 0.36-0.64. P-value = 0.0001) in favour of CMV. The most important pretreatment factors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
31
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(31 citation statements)
references
References 15 publications
0
31
0
Order By: Relevance
“…However, as grade 2 UC are still heterogeneous, there is a necessity to find new markers to subclassify grade 2 tumours. In the treatment of advanced stage bladder cancers, combination chemotherapy including platinum has revealed promising results (Mead et al, 1998). However, multidrug-resistant bladder cancer shows a poor prognosis.…”
mentioning
confidence: 99%
“…However, as grade 2 UC are still heterogeneous, there is a necessity to find new markers to subclassify grade 2 tumours. In the treatment of advanced stage bladder cancers, combination chemotherapy including platinum has revealed promising results (Mead et al, 1998). However, multidrug-resistant bladder cancer shows a poor prognosis.…”
mentioning
confidence: 99%
“…They concluded that although with cisplatin based multidrug chemotherapy response rates were high, the lack of randomised comparisons with best supportive care precludes definite conclusions regarding survival benefit gained. The differences observed in median survival between less intensive regimes (4.5 months with metotrexate/vinblastine [22]) and recent, more intensive chemotherapy (up to 13Á15 months with cisplatin based regimes [2]) however strongly suggests a survival benefit in selected patient groups. The basis on which to select patients for chemotherapy is however undocumented.…”
Section: Discussionmentioning
confidence: 96%
“…Unfi t patients represent 30% of patients with advanced disease [68]. Survival in "fi t" patients is over a year, with a complete response rate ranging from 15% to 30% [65,66]. Which CT is recommended for "fi t" patients?…”
Section: Treatment Of Metastatic Diseasementioning
confidence: 99%
“…Cisplatin-based combination CT is the standard care in the management of metastatic urothelial cancer [65,66]. The EORTC has categorised patients as either "fi t" for cisplatin or "unfi t" if they have poor renal function (creatinine clearance <60 ml/min), ECOG 2, grade 2 hearing loss, grade 2 neuropathy and/or New York Heart Association Class III heart failure [67].…”
Section: Treatment Of Metastatic Diseasementioning
confidence: 99%